Cognitive wireless communication network information sharing method based on blockchain technology. Issue 2 (5th June 2023) - Luo, Wei
Cognitive Wireless Network based on Blockchain Technology (CWN-BT) has been proposed in this paper. Blockchain strategies can provide encrypted communication networks for closed wireless transactions due to their multiple advantages, such as transaction speed, confidentiality, better security, increased performance, etc. Since each device in a blockchain depends on the data stored in a successive unit, it ensures secured transactions and resources in the wireless cognitive network. The outcome shows that blockchain helps to enhance wireless network security in different ways. Besides, integrating blockchain into a cognitive wireless communication network will make optimal capital and efficient network monitoring. The numerical findings demonstrate that the proposed CWN-BT model improves the data security level by 98.3%, the data transmission rate of 94.3%, an efficiency ratio of 96.7%, the response time of 95.6% and reduces the latency rate of 20.2%, delay rate of 17.2% compared to other popular models.